2004
DOI: 10.1029/2004jd004820
|View full text |Cite
|
Sign up to set email alerts
|

UV index climatology over the United States and Canada from ground‐based and satellite estimates

Abstract: [1] Long-term monthly mean UV index values for Canada and the United States were calculated using information from two sources: from noon erythemal UV estimated from Total Ozone Mapping Spectrometer (TOMS) total ozone and reflectivity data and from UV index values derived from observations of global solar radiation, total ozone, dew point, and snow cover. The results are presented as monthly maps of mean noon UV index values. Mean UV index values in summer range from 1.5 in the Arctic to 11.5 over southern Tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 41 publications
11
93
0
1
Order By: Relevance
“…Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014). However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012). In a recent study, Fragkos et al (2015) showed that in Thessaloniki, even under extreme high (low) total ozone column (TOC) conditions, the erythemal irradiance can be lower (higher) than its climatological values due to the dominant effect of aerosols.…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
See 2 more Smart Citations
“…Signs from the onset of ozone recovery since the late 1990s on surface UV-B irradiance have been mainly detected over the northern high latitudes; recent studies indicate that UV-B has been declining during the last 2 decades (Bernhard, 2011;Eleftheratos et al, 2014). However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012). In a recent study, Fragkos et al (2015) showed that in Thessaloniki, even under extreme high (low) total ozone column (TOC) conditions, the erythemal irradiance can be lower (higher) than its climatological values due to the dominant effect of aerosols.…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
“…However, during the same period, both the UV-B and the UV-A irradiance are increasing over many locations in the Northern Hemisphere mid-latitudes, mainly due to the negative trends in the amount of clouds and aerosols (De Bock et al, 2014;Fitzka et al, 2012;Román et al, 2015;Smedley et al, 2012;Zerefos et al, 2012). In a recent study, Fragkos et al (2015) showed that in Thessaloniki, even under extreme high (low) total ozone column (TOC) conditions, the erythemal irradiance can be lower (higher) than its climatological values due to the dominant effect of aerosols. Zerefos et al (2012) suggest that over Canada, Europe and Japan there is a statistically significant evidence of a slowdown or even a turning point in the upward UV-B trends after 2006, which is an indication that since then the negative trends of aerosols are no more the main driver of the long-term changes in UV-B irradiance.…”
Section: Fountoulakis Et Al: Short-and Long-term Variability Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…These estimates are affected by both instrumental errors and modelling uncertainties . Individual comparisons of satellite estimates with GB measurements has shown mainly a positive bias of TOMS, especially during summertime (Herman et al, 1999;Chubarova et al, 2002;Kazantzidis et al, 2005) and in some cases a negative bias in winter (Kalliskota et al, 2000;Fioletov et al, 2004). According to Herman et al (1999) and McKenzie et al (2001), TOMS produces systematically higher UV irradiance values at the northern midlatitudes, while in the Southern Hemisphere a better agreement with surface measurements has been found.…”
Section: Introductionmentioning
confidence: 83%
“…They concluded that TOMS UV retrievals have a positive bias between 1.4% and 12.5% at these sites. Fioletov et al [86] derived UV index climatologies for Canada and the USA using TOMS data for 1980-1990 and compared with Brewer measurements from several sites. They found that in summer the TOMS UV estimates were 10-30% higher than the Brewer measurements, most likely caused by air pollution and absorbing pollution.…”
Section: Satellite-derived Surface Uvmentioning
confidence: 99%